Toleransi logam berat timbal (Pb) pada bakteri indigenous dari air laut Pelabuhan Paotere, Makassar (Heavy metal lead [Pb] tolerance of indigenous bacteria from Seawater in Paotere Port, Makassar) - Fahruddin, Fahruddin; Santosa, Slamet; ., Sareda (AQUATIC SCIENCE & MANAGEMENT, 2020)
Marine water which has been polluted by heavy metals such as lead (Pb) from port activities can affect marine life, however several microorganisms are able to adapt in polluted waters due to their resistant capabilities. The research aimed to obtain isolates bacterial which are resistant to Pb and to test their resistant ability. Bacterial isolation was obtained from sediment and seawater taken in Paotere Port, Makassar. The isolation of the resistant bacteria was done using nutrient agar media which contained 10 ppm of Pb. The growth of the bacteria was initially observed macroscopically and microscopically to determine type of the colony. Resistant test for each type of isolate was done by inoculating them on nutrient broth media which contained different concentration of Pb: 5 ppm, 10 ppm, 15 ppm, 20 ppm, 25 ppm, and a control. The test resulted in eight different isolates, five isolates from sediment samples and three from seawater samples. The results showed that each isolate has different degree of resistant toward Pb. Isolate IA1 has the higher resistant ability, and it was followed by isolate IS5.---Perairan laut tercemar logam berat timbal (Pb), yang bersumber dari aktifitas pelabuhan, dapat mengganggu kehidupan biota laut, namun sejumlah mikrorganisme mampu beradaptasi karena memiliki kemampuan resistan.Â  Penelitian ini bertujuan untuk memperoleh isolat bakteri yang resistan terhadap Pb dan menguji kemampuan resistansinya. Isolasi bakteri diperoleh dari sampel sedimen dan air laut dari Pelabuhan Paotere, Makassar.Untuk isolasi bakteri resistan menggunakan media nutrient agar yang megandung 10 ppm Pb. Bakteri yang tumbuh diamati secara makropskopis dan mikroskopis sebagai pendekatan awal untuk mengetahui jenis isolat. Uji resistansi dilakukan untuk setiap jenis isolat, yang diinokulasikan pada media nutrient broth pada konsentrasi Pb sebesar 5 ppm, 10 ppm, 15 ppm. 20 ppm, 25 ppm dan 0 ppm sebagai kontrol.Â  Hasilnya, diperoleh delapan jenis isolat yang berbeda, yaitu lima jenis isolat dari sampel sedimen dan tiga dari sampel air laut. Dari hasil uji memperlihatkan, bahwa setiap isolat memiliki kemampuan resistansi berbeda-beda terhadap Pb. Isolat IA1 kemampuan resistansinya lebih tinggi, kemudian isolat IS5.